Analisis Pemanfaatan Hasil Riset dalam Perencanaan Pembangunan Daerah Kabupaten Sikka - Eufrasia Octriancy Yohendri; Yosefina Andia Dekrita; Imelda Virgula Wisang (Dharma Ekonomi, 2024)
This study aims to find out how to use research results in Sikka Regency Regional Development Planning. The problems faced are limited human resources, minimal budget for research and development activities, low coordination between research institutions and the government, and the results of recommendations from research that are not optimal. The research method used is a qualitative method. Data collected through interviews and analyzed qualitatively. The results of this research show that analysis of the use of research results is important to increase the effectiveness and efficiency of development programs, reduce uncertainty, and minimize the risk of failure in Sikka Regency Regional Development Planning.